ENTROPY-BASED FUZZY AHP SEBAGAI PENDUKUNG KEPUTUSAN PENEMPATAN BIDAN DI KOTA BANJARBARU - Siti Hatimah Rahmadaniah; Oni Soesanto; Dwi Kartini (Lambung Mangkurat University, 2015)
Banjarbaru City Health Office is a government agency that plays an important role in health development in Banjarbaru. Support system midwife placement in the Health Service Banjarbaru done by following the specified criteria. However, the system has not been run in accordance with these criteria, but every midwife who will be placed in primary and villages are given the freedom to choose from one health center placement options, and direct placement was decided on the option selected health centers midwives. Because of the ineffectiveness of the existing system at the Department of Health Banjarbaru it will be designed and built